2016
DOI: 10.1007/s11096-016-0272-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating antidepressant treatment prior to adding second-line therapies among patients with treatment-resistant depression

Abstract: Many patients do not receive an adequate antidepressant trial before starting a second-line agent. The type of second-line treatment was independent of severity of depression. These findings support policies that require reviewing the recommended dose and duration of the first-line antidepressant before adding second-line agents. Healthcare providers need to review the patient's history and reconsider the evidence for prescribing second-line agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Patients must also have had a diagnosis for MDD [any inpatient or outpatient ICD-9CM 296.2x, 296.3x, 300.4, or 311 (Fiest et al, 2014)] and have had filled at least one SSRI or SNRI during the pre-index period. Those with any diagnosis of schizophrenia (295.xx), bipolar disorder (296.0x, 296.1x, 296.4x-296.8x) (Hartung et al, 2013), dementia (290.xx), delusional disorder (297.xx), non-organic psychosis (298.xx), autism (299.0), mental retardation (317.0-319.0), cerebral degeneration (331.xx), Parkinson’s disease (332.xx), senility without mention of psychosis (797.0) (Hassan, Farmer, Brahm, & Neas, 2016a), or thyroid disorder (240.0-246.0) during the pre-index period were excluded. Patients who have had a prescription filled for clozapine, a first generation antipsychotic, or an injectable SGA during the pre-index period were also excluded, since use of these medications typically represents underlying psychosis.…”
Section: Methodsmentioning
confidence: 99%
“…Patients must also have had a diagnosis for MDD [any inpatient or outpatient ICD-9CM 296.2x, 296.3x, 300.4, or 311 (Fiest et al, 2014)] and have had filled at least one SSRI or SNRI during the pre-index period. Those with any diagnosis of schizophrenia (295.xx), bipolar disorder (296.0x, 296.1x, 296.4x-296.8x) (Hartung et al, 2013), dementia (290.xx), delusional disorder (297.xx), non-organic psychosis (298.xx), autism (299.0), mental retardation (317.0-319.0), cerebral degeneration (331.xx), Parkinson’s disease (332.xx), senility without mention of psychosis (797.0) (Hassan, Farmer, Brahm, & Neas, 2016a), or thyroid disorder (240.0-246.0) during the pre-index period were excluded. Patients who have had a prescription filled for clozapine, a first generation antipsychotic, or an injectable SGA during the pre-index period were also excluded, since use of these medications typically represents underlying psychosis.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, they can help in distinguishing treatment resistance from inadequate treatment. Multiple studies have found non-adherence to antidepressants to be as high as 40-50% in community samples 145146147. Some evidence suggests that most patients considered to have TRD in primary care have not had drugs prescribed at the recommended doses or for the recommended length of time or have not taken them as prescribed 148.…”
Section: Ongoing Managementmentioning
confidence: 99%
“…The treatment plan can be revised by implementing one of several therapeutic options, including optimizing the initial treatment, adding a drug that is not traditionally used as an antidepressant (augmentation), changing to a different treatment (switch), or combining two or more antidepressants [1,7,130,137139]. …”
Section: Expert Commentarymentioning
confidence: 99%
“…Indeed, accurately identifying TRD is a prerequisite for optimally changing treatment regimens to help patients achieve remission [139]. Evidence indicates that large numbers of depressed patients are undertreated, resulting in prolonged episodes and the appearance of ‘pseudo-resistance’ [2,150].…”
Section: Five-year Viewmentioning
confidence: 99%